Fabrication of Cookle Shell-Based 3D Scaffolds for Bone Repair - Hussein Al-Hussany, Bahaa Fakhri (2010)
The work presented in this thesis focused on bone tissue engineering approach as an alternative treatment for bone repair and losses resulting from injury or disease. This multidisciplinary field combines biology, engineering, physics, materials sciences, and medicine, to develop bone tissue like substitutes. This is achieved through a specific interaction between scaffolds, cells and growth factors. Thus, there are three key issues that lead to the design of successfully engineered bone tissue, and must be carefully investigated. The main objective proposed in this thesis addresses the fabrication of artificial bone tissue, and in vitro and in vitro tests to confirm the suitability of the fabricated bone tissue. The research works were divided into three parts. The results obtained in each part contributed significantly to engineering area of bone tissue. The first part was directed towards the development of a new scaffold used in bone tissue engineering. The second part of this work focused on bone cell attachment and growth on the scaffold in vitro. The third part focused on the post-implantation biological evaluation of the implanted newly developed scaffold in vivo. Three-dimensional novel porous biodegradable scaffolds were fabricated with micro and macro-architectures. For the first time, a unique blend of cockle shell, dextrin, dextran and gelatin were studied in order to design an ideal bone scaffolds with an adequate degradation rate. Five different ratios of bone scaffolds were rabricated and two different processing methods were used to develop the scaffolds. The processing methods used in this study allowed the preparation of 3D-Scaffolds with controlled porosity and adequate pore size with good mechanical strength. The newly developed scaffolds have the following characteristics: (i) good biocompatibility and biodegradability, (ii) suitable surface chemistry and (iii) highly porous, with interconnected pore net work. In vitro study on rabbit bone marrow osteoblastic differentiation of stromal cells (MSC) was assessed on scaffolding. The MSCs was cultured for 10 to 16 days using fresh cells of bone marrow under osteogenic differentiation conditions. The cells were sub-cultured for 5 weeks on different compositions of the scaffolds. The capability of cells to proliferate and form extracellular matrix on these scaffolds was assessed by a significantly increased activity of alkaline phosphatase and calcium deposits at 21 days. Light and scanning electron microscopy revealed the presence of numerous osteoblasts-like cells with the development of calcification of the dense network of collagen fibrils and bone matrix-like tissues were observed in the different area of scaffolds, resulting in the formation of bone like tissue containing osteocyte-like cells. In this process the manual delivery of nutrients and disposal of waste were applied. In vivo study was about evaluating the new bioceramic scaffolf. Various micro-macropores scaffolds were implanted into 1.5 cm critical size defect created on the radial bone of rabbits. Bone regrowth in the bioceramics was obtained using an established model of bone formation in vitro by exogenously added osteoprogenitor cells. Radiographic examination revealed new bone image representing the bone construct was formed at the margin and centre of the defect, which involved osteogenesis that diffused from the central region and the margin of the scaffold implant. Histological analysis of samples at 8 weeks revealed the amount of mature bone had increased to form completer bone. The mass of the implanted scaffold was completely dissolved and absorbed during this time. A little cartilage tissue was detected in some of the implanted scaffolds. Bone formation showed a centripetal pattern, and the new bone always appeared as a replacement to the implanted matrix. As far as we know, the time of complete restore the lost bone in this study represents a major break through in the artificial bone graft healing.